1991
DOI: 10.1002/eji.1830210805
|View full text |Cite
|
Sign up to set email alerts
|

Preferential development of pre‐B lymphomas with drastically down‐regulated N‐myc in the Eμ‐ret transgenic mice

Abstract: We established one transgenic mouse line which developed pre-B leukemic lymphomas by introducing ret cDNA driven by the SV40 promoter and the mouse immunoglobulin (Ig) enhancer. Lymphomas developed not only in the lymph nodes and the spleen but also in the thymus between the ages of 7 and 21 weeks. Analyses of cell surface phenotypes and Ig gene rearrangement revealed that these tumors were surface IgM-B220+ pre-B lymphomas. The rearrangement pattern of the Ig heavy chain locus indicated that the tumor cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Ongoing deletion of all B-lymphoid programmed leukaemia through CD19 immune pressure or genetic ablation reveals the myeloid potential. This is in contrast to the Eμ-RET-driven leukaemia, that is driven by an Eμ-enhancer and lacks a myeloid potential in several publications 41 53 54 , and which retains stable B lineage commitment even with in vivo CD19-CAR immune pressure or in vitro deletion of Ebf1 and Pax5 .…”
Section: Discussionmentioning
confidence: 73%
“…Ongoing deletion of all B-lymphoid programmed leukaemia through CD19 immune pressure or genetic ablation reveals the myeloid potential. This is in contrast to the Eμ-RET-driven leukaemia, that is driven by an Eμ-enhancer and lacks a myeloid potential in several publications 41 53 54 , and which retains stable B lineage commitment even with in vivo CD19-CAR immune pressure or in vitro deletion of Ebf1 and Pax5 .…”
Section: Discussionmentioning
confidence: 73%
“…Typically, such immature IgM Ϫ B or DP/TCR low T lymphoma cells are able to escape the boundaries of their normal somatic environment (bone marrow or thymus, respectively) and spread to blood and peripheral organs. Similar attributes are shared by lymphomas arising in many other transgenic models in which oncogenes are targeted to lymphoid tissues, including E-myc (46,47), E-ret (48,49), and lck-M cyclin (44). In all cases, it remains unclear whether the primary action of the oncogenic lesion is to promote cell proliferation and/or to suppress differentiation.…”
Section: Discussionmentioning
confidence: 74%
“…The results of our earlier experiments suggested that the RET oncogene product works not only for promoting oncogenesis but also for inducing anti-tumor protective immunity (Ichihara et al, 1995;Kato et al, 1999). As shown in Figure 1(A), growth of transplanted Ret lymphoma cells, which were derived from an Em/RET-transgenic mouse (Iwamoto et al, 1991), was strongly suppressed in recombinant Ret protein-immunized, but not non-immunized, genetically compatible recipient mice. This ®nding corresponds to our previously reported ®nding of Ret protein expressed on tumors acting as a transplantation tumor antigen (Ichihara et al, 1995;Kato et al, 1999).…”
Section: Replymentioning
confidence: 87%